Knowledge hiding behavior in higher education institutions: a scientometric analysis and systematic literature review approach - Muhammad Ashraf, Fauzi (Emerald Publishing Limited, 2022)
Purpose – The purpose of this paper is to systematically review knowledge hiding (KH) behavior in higher education institutions (HEIs). KH is regarded as an unethical and antisocial behavior by many scholars, which should not be prevalent in HEIs.